Postnatal care utilization in the Oshana region of Namibia: Prevalence, associated Factors, and a decision framework - Enos Moyo; Perseverance Moyo; Tafadzwa Dzinamarira; Grant Murewanhema; Andrew Ross (Elsevier, 2024)
Background: Namibia faces a persistent challenge of high maternal and neonatal mortality, particularly within the postnatal period. This study assessed postnatal care (PNC) utilization prevalence in Namibia's Oshana region, identified influencing factors, and aimed to develop a decision framework for healthcare providers to predict women who are unlikely to utilize PNC. Methods: A quantitative cross-sectional survey employing a systematic random sample (n = 814) and self-administered questionnaires was conducted. Data analysis employed Chi-squared tests, bivariate and multivariate logistic regression, and classification tree analysis. Results: PNC utilization was 43.8 %, 95 % (CI 40.3 % - 47.3 %). Respondents who stayed in rural areas and the unemployed were less likely to utilize PNC services, AOR = 0.51, 95 % CI (0.35 - 0.74) and AOR = 0.26, 95 % CI (0.17 - 0.40), respectively. Respondents with poor PNC knowledge and poor PNC perception were less likely to utilize PNC services, AOR = 0.63, 95 % CI (0.41 - 0.98) and AOR = 0.32, 95 % CI (0.21 - 0.49), respectively. Classification analysis revealed mode of delivery, employment status, and marital status as significant predictors of PNC utilization. Conclusion: Expanding healthcare facilities in rural areas, empowering women through education and income-generating projects, and utilizing community health workers for PNC education are crucial strategies to improve utilization rates.